2017
DOI: 10.1155/2017/6739236
|View full text |Cite
|
Sign up to set email alerts
|

MNRR1, a Biorganellar Regulator of Mitochondria

Abstract: The central role of energy metabolism in cellular activities is becoming widely recognized. However, there are many gaps in our knowledge of the mechanisms by which mitochondria evaluate their status and call upon the nucleus to make adjustments. Recently, a protein family consisting of twin CX9C proteins has been shown to play a role in human pathophysiology. We focus here on two family members, the isoforms CHCHD2 (renamed MNRR1) and CHCHD10. The better studied isoform, MNRR1, has the unusual property of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 92 publications
2
16
0
Order By: Relevance
“…FGF21 and HTRA2 orthologous genes ( fgf21 , htra2 ) were also significantly upregulated in the double chchd10 -/- & chchd2 -/- model (Fig. 7 B) as was the previously described oxygen responsive transcript, cox4i2 (2527) (Fig. 7 C).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…FGF21 and HTRA2 orthologous genes ( fgf21 , htra2 ) were also significantly upregulated in the double chchd10 -/- & chchd2 -/- model (Fig. 7 B) as was the previously described oxygen responsive transcript, cox4i2 (2527) (Fig. 7 C).…”
Section: Resultssupporting
confidence: 56%
“…CHCHD2 and CHCHD10 share 58% sequence identity and have a common ancestor in yeast, suggesting that these proteins might have partially overlapping function (15). In vitro studies have reported that loss of either CHCHD2, CHCHD10 or both, impacts mitochondrial respiration (10, 16), survival/growth following exposure to various cellular stressors (9, 10, 16, 17), the mitochondrial integrated stress response (mt-ISR) (1822), apoptosis (23, 24), as well as the transcription of the oxygen responsive gene COX4I2 (2527).…”
Section: Introductionmentioning
confidence: 99%
“…Exosome Hypoxia also downregulated the expression levels of Mtfp1, a participant in Dox-induced cardiac injury [64]. While, exosome Hypoxia increased the expression levels of Hspa1a (autophagy inducer) [65], Cox4i2 (the modulator of mitochondrial response) [66], and ATP1B2 (cardiac oxidative stress inhibitor) [67], accompanied by cellular rejuvenation. Also, these metabolism-related genes were the target genes of miR-92a-3p to maintain cardiac metabolism homeo-stasis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Next, CHCHD2 was identified as a prime candidate linking Bcl-xL to the transcriptomic changes, because it is consistently downregulated in mutant cells and the protein binds Bcl-xL, resulting in a decreased oligomerization of Bax (Liu et al., 2015). This downregulation may be through a self-regulatory feedback loop, as CHCHD2 is able to translocate to the nucleus to transactivate itself as well as other genes that contain oxygen-responsive element sequences in their promoter region (Aras et al., 2013, Grossman et al., 2017). Another interesting function of CHCHD2 is its capacity to interact with the SMADs (2/3/4) and thus modulate the transcription of TGF-β-mediated target genes (Zhu et al., 2016).…”
Section: Discussionmentioning
confidence: 99%